Coping strategies in undergraduate daily life and mental health care - Lopes de Faria, Elisângela (2026)
Introduction: Undergraduate studies represent a transitional phase in students’ lives, and the challenges involved require adaptation to university routines and time management; Objective: to understand how undergraduate students cope with daily academic life and care for their mental health from their own perspective; Method: this is a qualitative study, based on Grounded Theory and Symbolic Interactionism, involving 35 undergraduate students; Results: the findings highlight coping strategies for the difficulties experienced and adaptation to academic life, stemming from students’ proactivity, prioritization, self-demand, support from peers, some faculty members and course coordinators, family, and spirituality; Final considerations: it is considered that the challenges faced by undergraduates in their daily lives should be acknowledged within the institutional environment, paying attention to the contexts in which they occur and the ways to address them, with appropriate institutional and collective support.